The Effect of Brand Image, Product Quality, and Price on Customer Loyalty Through Customer Satisfaction on Brand in the City of Bengkulu - Asdhion, Alessandro; Badruddin, Redy; Trisusilo, Agung (Musamus Journal of Agribusiness, 2025)
As time progresses, humans are busy with activities every day. Urban communities tend to have poor lifestyles, especially in terms of diet. The existence of the YKLT (YKL) brand of fermented milk is one solution for maintaining body immunity during busy urban lives. This research aims to determine the influence of brand image, product quality, and price on consumer loyalty through consumer satisfaction with YKLT products. This research was conducted on consumers who consumed YKLT products in Bengkulu City. The number of samples taken in this research was 96 respondents using purposive sampling technique, data was collected by distributing questionnaires. The analytical method used is SEM (Structural Equation Modeling). The PLS (Partial Least Square) approach uses SmartPLS 3.0 software. The analysis results show that consumer satisfaction is not influenced by brand image (X1), but rather by product quality (X2) and price (X3). The X variables do not affect consumer loyalty. However, product quality and price can influence consumer loyalty if mediated by customer satisfaction.